2004
DOI: 10.1115/1.1767814
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Self-Loosening of Bolted Joints

Abstract: The self-loosening process of a bolted joint consists of two distinct stages. The early stage of self-loosening is due to the cyclic plastic deformation of the materials. The second stage of self-loosening is characterized by the backing off of the nut. The current work is concentrated on an experimental investigation of the second stage self-loosening. Over one hundred bolted joints with M12×1.75 bolts and nuts were experimentally tested using a specially designed testing apparatus. The experiments mimicked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 8 publications
2
42
0
Order By: Relevance
“…However, this ideal clamping behaviour is hard to maintain due to time-dependent features such as changes in material properties and the condition of contact surfaces [19,20,57,58]. The self-loosening process starts with the gradual relaxation of initial preload.…”
Section: Failure Analysis Of Ltts Subject To Static Loads Bolted Connmentioning
confidence: 99%
“…However, this ideal clamping behaviour is hard to maintain due to time-dependent features such as changes in material properties and the condition of contact surfaces [19,20,57,58]. The self-loosening process starts with the gradual relaxation of initial preload.…”
Section: Failure Analysis Of Ltts Subject To Static Loads Bolted Connmentioning
confidence: 99%
“…There has been much research on this topic. Self-loosening mechanisms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and their various influencing factors [17][18][19][20][21] were studied through experiments, theoretical analyses and numerical simulation. A variety of measures were proposed to prevent self-loosening, such as chemical locking [21], step lock bolt (SLB) [22], and double-nut [8,23].…”
Section: Introductionmentioning
confidence: 99%
“…The initial loss of the clamping force was attributed to the repeated twist of the nut relative to the bolt shank because of the slippage between the bolt and nut threads. Yanyao Jiang and Ming Zhang [6,7] proposed that bolted joints will occur self-loosening based on the experiments, and revealed that the self-loosening process can be divided into two distinguishable stages. The first stage is featured by a short and sharp clamping force reduction with no relative rotation between the nut and the bolt.…”
Section: Introductionmentioning
confidence: 99%